Polimorfismos da metilenotetrahidrofolato redutase e sua associação com fatores de risco para doenças crônicas não transmissíveis na Coorte de 1982, Pelotas, RS, Brasil - Silva, Liziane Pereira da (2013)
Methylenetetrahydrofolate Reductase (MTHFR) gene polymorphisms are related to low activity of the enzyme increasing homocysteine (Hcy) plasma levels. Hyperhomocysteinemia (HHcy) is a risk factor for several pathological processes including atherosclerosis. The aim of the present study was to evaluate the effect of MTHFR C677T and A1298C polymorphisms and behavioral factors on Hcy levels in 3831 biological samples from 1982 Pelotas Birth Cohort individuals. The Hcy levels were measured in serum samples using chemiluminescence immunoassay. The genotyping was performed by allelic discrimination technique using pre-designed TaqMan® assays in the ABI7500 Fast Real-Time PCR System. The mean levels of Hcy were higher (p<0.001) in homozygous TT variant of MTHFR C677T than in CT and CC genotypes independently of sex, alcohol consumption, smoking and physical activity during leisure time. However it was demonstrated a higher MTHFR 677TT effect in smokers compared to non-smokers, as well as, in alcohol consumers than in non-consumers and in active individuals than in less active ones (p for interaction <0.001, respectively). For the MTHFR A1298C, the Hcy levels were higher in AA genotype than AC and CC genotypes, independently of behavioral factors. Men genotyped as MTHFR 1298AA showed 14% increasing on Hcy levels compared to 4% increase observed in women (p for interaction <0.001). No interactions were demonstrated between this polymorphism and the other behavioral factors analyzed. In conclusion, in young adult from 1982 cohort it was observed an interaction effect between the MTHFR C677T polymorphism and lifestyle on Hcy levels, contributing to an increased risk for cardiovascular chronic diseases in the future.